أثر تقرير محافظ الحسابات في تعزيز تطبيق حوكمة الشركات في المؤسسات الاقتصادية الجزائرية - عبداللاوي، نور الهدى; عطاوي، الهام (جامعة الوادي University of Eloued, 2025)
The study aims to measure the impact of the auditor's report on enhancing the application of corporate governance principles in Algerian economic institutions. A questionnaire was distributed to 35 auditors, and the data were analyzed using SPSS software. The results showed that the auditor's report has a significant impact of 72.2% in improving corporate governance, playing a fundamental supervisory role in supporting its proper application. The report also enhances disclosure and transparency by providing accurate and reliable information, protecting shareholders' rights, and increasing their confidence in the institution. Furthermore, the report helps the board of directors to effectively fulfill its responsibilities by addressing weaknesses, ensuring compliance with laws, and strengthening the institution's ability to achieve its goals.
The Impact of the Auditor's Report on Enhancing the Implementation of Corporate Governance in Algerian Economic Institutions. -A Study of a Sample of Auditors
مقال
Keywords: تقرير محافظ الحسابات; حوكمة الشركات; الإفصاح والشفافية; حقوق المساهمين; مجلس الإدارة; disclosure and transparency; auditor's report; board of directors; shareholders' rights